Enhancing visitor experience using service design approach for museum sustainability/ Ana Baidza Abu Bakar and Muhammad Zaffwan Idris - Abu Bakar, Ana Baidza; Idris, Muhammad Zaffwan (Universiti Teknologi MARA, Perak, 2024)
Countries all over the world have recognised museums' functions in showcasing a country's background, historical moments, and significant events where it can provide a fascinating glimpse into its history and tradition, bringing us to the highlights of a country's achievement. As a result, many countries began to develop their museums to be more focused on delivering visitor-oriented services in order to attract more visitors, which is supported by numerous recent studies on the museum and/or visitor experience. Currently, museums are expected to provide better services by providing positive experiences and satisfaction to visitors which may reverberate on the brand royalty, resulting in visitors returning to the museums. These circumstances will offer free advertising through the museum's visibility on the public radar in the future for attracting newcomers. Understanding visitors' visiting styles, behaviours, needs, and motivations is critical because it provides details on visitors' expectations while also understanding the visitor experience, all of which can be aptly accomplished using the service design approach. The foundation of this paper will be a proposed framework for museum experience based on service design, as it is performed using service design tools such as personas and customer journey maps, which will benefit the museum institution by observing visitors' perspectives and thus improving museum services. Finally, it is believed that observing museums' capability as a service provider from the visitors' perspectives while considering museums' intentions will benefit museums in the long run, while also ensuring their sustainability as a major contributing factor to the tourism industry, which is in line with the current consumerism trend.